Penerapan Algoritma Sequential Search pada Aplikasi Kamus Bahasa Ilmiah Tumbuhan - Rahmanto, Yuri; Alfian, Joni; Damayanti, Damayanti; Borman, Rohmat Indra (Jurnal Buana Informatika, 2021)
Abstract. Application of Sequential Search Algorithms in the Plant Scientific Language Dictionary Application. Scientific dictionaries such as plants dictionaries are thick and less attractive. Therefore, it is necessary to develop a scientific language dictionary application for plant which is attractive and can be accessed anytime and anywhere. The dictionary application is closely related to the search feature and the sequential search algorithm is used in the search feature at the application development. This algorithm performs the search by matching data in a row from all existing data. The application built had features such as a list of plants with scientific names equipped with A-Z alphabet menus, plant categories, and a search feature to make it easier for users to find the plant names. The results of the search speed performance test based on page load time with the microtime function show that sequential search algorithms can perform the searches quickly for relatively limited and not too much data.Keywords: Scientific Language Dictionary, Plant Dictionary, Sequential Search Abstrak. Kamus ilmiah seperti kamus ilmiah tumbuhan berbentuk tebal dan kurang menarik. Oleh karena itu, diperlukan pengembangan aplikasi kamus Bahasa ilmiah tumbuhan yang menarik dan dapat diakses kapanpun dan dimanapun. Aplikasi kamus akan berhubungan erat dengan pencarian dan algoritma sequential search digunakan sebagai fitur pencarian pada pengembangan aplikasi kamus bahasa ilmiah tumbuhan ini. Algoritma ini melakukan pencarian dengan mecocokan data secara beruntun dari seluruh data yang ada. Aplikasi yang dibangun memiliki fitur-fitur seperti daftar tumbuhan dengan nama ilmiah yang dilengkapi menu abjad A-Z , kategori tumbuhan, dan fitur pencarian untuk memudahkan pengguna dalam menemukan nama tumbuhan. Hasil pengujian kecepatan pencarian berdasarkan page load time dengan fungsi microtime menunjukkan bahwa algortima sequential search dapat melakukan pencarian dengan cepat untuk data yang relatif terbatas atau tidak terlalu banyak.Kata Kunci: Kamus Bahasa Ilmiah, Kamus Tumbuhan, Sequential Search